The Duty to Consult in Canada Post-Haida Nation - Nigel Bankes (Arctic Review on Law and Politics, 2020)
This article is intended as a companion piece to Øyvind Ravna’s contribution to this anniversary volume. It maps the development of the duty to consult in Canadian law since the seminal decision of the Supreme Court of Canada in Haida Nation v British Columbia in 2004. The article begins by briefly examining the first references to the duty to consult in 1990 before turning in Part 2 to the transformation of the duty in Haida Nation and a doctrinal analysis of the various elements of the duty. Part 3 examines the international standard of free, prior and informed consent (FPIC) as developed in the UN Declaration on the Rights of Indigenous Peoples as well as the implications of legislation that aims to give effect to the Declaration in federal or provincial law. The conclusion to the paper offers some comparative comments on Norway and Canada regarding the development of the duty to consult. These comments emphasise that whereas consultation and FPIC obligations in Norway are firmly rooted in international law, and, in particular, in the International Labour Organization’s Convention on Indigenous and Tribal Peoples (ILO C-169), this is not the case in Canada. In Canada, the duty to consult and accommodate finds its origins in domestic law and the entrenchment of aboriginal rights in the Constitution in 1982. However, more recent discussions over the implementation of the UN Declaration in federal and provincial law have inevitably broadened the discourse to include international law and the FPIC standard.